2020
DOI: 10.3390/nano10102078
|View full text |Cite|
|
Sign up to set email alerts
|

Non-Absorbing Dielectric Materials for Surface-Enhanced Spectroscopies and Chiral Sensing in the UV

Abstract: Low-loss dielectric nanomaterials are being extensively studied as novel platforms for enhanced light-matter interactions. Dielectric materials are more versatile than metals when nanostructured as they are able to generate simultaneously electric- and magnetic-type resonances. This unique property gives rise to a wide gamut of new phenomena not observed in metal nanostructures such as directional scattering conditions or enhanced optical chirality density. Traditionally studied dielectrics such as Si, Ge or G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 156 publications
(134 reference statements)
0
3
0
Order By: Relevance
“…Nanoparticles are most widely used in medicine [ 23 , 24 ], spectroscopy [ 25 , 26 ], catalysis [ 27 , 28 ], and energy [ 29 , 30 ]. Catalysis and energy fields are of main interest in this paper, since the development of advanced catalysts based on metal nanoparticles with improved activity, selectivity and stability is an important and relevant task [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles are most widely used in medicine [ 23 , 24 ], spectroscopy [ 25 , 26 ], catalysis [ 27 , 28 ], and energy [ 29 , 30 ]. Catalysis and energy fields are of main interest in this paper, since the development of advanced catalysts based on metal nanoparticles with improved activity, selectivity and stability is an important and relevant task [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, as a result of their relatively large losses and limited frequency ranges, a broad spectrum of materials is currently being explored as low-loss alternatives for expanding resonances into the UV, mid-IR, and THz regimes. These include, but are not limited to, doped oxides, ceramics, high refractive index (HRI) semiconductors, chiral assemblies, 4 and 2D materials. These developments also include new possibilities for controlling the direction of scattered light by capitalizing on coherent interactions between electric and magnetic resonances.…”
Section: Introductionmentioning
confidence: 99%
“…In the published study [ 1 ], a mistake was reported in the method of obtaining the mean value over the spherical nanoparticle surface of the near-field enhancement (NFE, ) and the optical chirality density (OCD, ). Recently, we have been advised that the way we obtained the mean values is incorrect: The mean value of the dispersion of points is obtained from the evaluation of the OCD and NFE using the coordinates generated on the surface of the sphere from a homogeneous 2D mesh grid in the polar angles .…”
mentioning
confidence: 99%